2014
DOI: 10.1371/journal.pone.0108187
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of T-Type Ca2+ Channels in Spinal Motoneurons of the Adult Turtle

Abstract: Voltage-gated Ca2+ (CaV) channels are transmembrane proteins comprising three subfamilies named CaV1, CaV2 and CaV3. The CaV3 channel subfamily groups the low-voltage activated Ca2+ channels (LVA or T-type) a significant role in regulating neuronal excitability. CaV3 channel activity may lead to the generation of complex patterns of action potential firing such as the postinhibitory rebound (PIR). In the adult spinal cord, these channels have been found in dorsal horn interneurons where they control physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Second, although the functional expression of Ca v 3.2 in mammalian motor neurons remains elusive, several studies suggest that T-type channels may have a functional role. For instance, Ca v 3.1 channels are present in turtle spinal motor neurons where they contribute to cellular excitability [34]. In addition, a low-threshold voltage-activated calcium conductance was reported at nodes of Ranvier in mouse spinal motor neurons, suggesting the presence of T-type channels [35].…”
Section: Discussionmentioning
confidence: 99%
“…Second, although the functional expression of Ca v 3.2 in mammalian motor neurons remains elusive, several studies suggest that T-type channels may have a functional role. For instance, Ca v 3.1 channels are present in turtle spinal motor neurons where they contribute to cellular excitability [34]. In addition, a low-threshold voltage-activated calcium conductance was reported at nodes of Ranvier in mouse spinal motor neurons, suggesting the presence of T-type channels [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our observation that the p.V681L and p.D1233H mutations caused a reduction of the window current could have an important consequence at early stages of muscle differentiation and may represent an underlying mechanism of infantile-onset amyotrophy ( Figure 5(a)). Additionally, several studies have reported the expression of T-type channels in motor neurons [31,32]. Although the role of T-type channels in motor neurons has not been investigated yet, it is likely that they contribute to some forms of neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have reported the expression of T-type channels in motor neurons,119 120 the functional implication of T-type channels in these neurons has yet to be analysed. Increased neuronal excitability has been reported as a hallmark in ALS, where an increase of the sodium conductance and a decrease of axonal potassium currents is observed 121.…”
Section: Cacna1h (Cav32) Channelopathiesmentioning
confidence: 99%